Identifikasi Anatomi Aksara Lampung - Refita Ika Indrayati; Namuri Migotuwio (AKSA: Jurnal Desain Komunikasi Visual, 2020)
Writing system in a form of script is an integral part ofcommunication. Its existence enabling history, idea and knowledgeto spread beyond one’s land and passed from one generation to theother. As a part of Indonesian culture, Lampung script of HadLampung must be preserved. But in reality, the usage of this script isfading from society. The difficult writing system and wide-spreadusage of Latin alphabet as standard in Indonesian language aresome of the factors why Lampung script is not a popular writingsystem in Lampung. This research is trying to fill the gap betweenthe effort of conservation and the lack of documentation about localscript. This study uses Type Design Parameter by Mohanty toidentify and categorize Lampung script anatomy. This identificationcan be guideline recommendation for Lampung script basedtypography design and other purposes.